Barrie Kosky’s The Lost Echo: rethinking tragic catharsis through affective emergenc(e)y - Farrell, Charlotte (Peripeti, 2012)
Taking as her point of departure Barrie Kosky’s ’post tragedy’ "The Lost Echo" and referring to the concept of ’affective emergenc(e)y’ Charlotte Farrell argues for a rethinking of the Aristotelian concept of tragic catharsis and the distinction between audience and performance, subject and object traditionally associated with this concept.